Conference "Spatialities": Reimagining Territoriality (Conference Spatilities 2023, 2024)
Conference session including launch of documentary video Convenors: Valerie V. V. Gruber & Gilbert Shang Ndi Discussants: Dandara Maia Schellenberg & Hamissou Rhissa Achaffert In the backdrop of the historical uprooting and the forced deportation of Africans to the Americas, territoriality has become key in analysing practices of Afro-descendant resistance and (re-)existence in the Latin-American diaspora. It is in the re-making and re-imagining of (post)colonial territories that insurgent knowledges are produced, especially in contexts where the legacies of enslavement, marginalisation and invisibilisation are rife. Inspired by the ways in which young artists from Cartagena de Indias (Colombia) and Salvador da Bahia (Brazil) re-invent territoriality through artistic creativity, we developed a Participatory Action Research project that harnesses community mapping, self-writing and performance in an online and on-site exchange programme. In this panel conducted at the annual Cluster conference 2023 on Spatialities, Valerie Gruber and Gilbert Ndi Shang launch and discuss the documentary video "MemoriAmefricana – Cartagena de Indias/Salvador da Bahia" on this collective process realised in collaboration with the socio-cultural groups Candilé (Colombia) and REPROTAI (Brazil). In a self-reflexive mode that casts a critical glance at our transdisciplinary co-creation of knowledges, we focus on the challenges, shortcomings as well as opportunities of doing Participatory Action Research in actual and virtual spaces for more than three years. Thereby, we bring into dialogue the perspectives of two project coordinators and two discussants who followed the process with interest, though not actively involved. The team considers the participatory exploration of territories and territorialities as a pertinent heuristic prism in examining Afro-diasporic lifeworlds and the practical/symbolic attempts at memorialisation and collective becoming. Through creative media, youth and young adults re-map possibilities of existence that envision more inclusive spaces, using traces of African heritage as building blocks for individual and collective self-actualisation. This session is the outcome of research conducted within the Africa Multiple Cluster of Excellence at the University of Bayreuth, funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany's Excellence Strategy – EXC 2052/1 – 390713894. It was recorded during the International Conference "Reconfiguring African Studies through Spatialities" at the University of Bayreuth (Germany) on October 12, 2023.